The relative importance of concurrent writers and weak consistency models - Keleher, P.J. (Proceedings of the 16th International Conference on Distributed Computing Systems, 1996)
This paper presents a detailed comparison of the relative importance of allowing concurrent writers versus the choice of the underlying consistency model. Our comparison is based on single- and multiple-writer versions of a lazy release consistent (LRC) protocol, and a single-writer sequentially consistent protocol, all implemented in the CVM software distributed shared memory system. We find that in our environment, which we believe to be representative of distributed systems today and in the near future, the consistency model has a much higher impact on overall performance than the choice of whether to allow concurrent writers. The multiple writer LRC protocol performs an average of 9% better than the single writer LRC protocol, but 34% better than the single-writer sequentially consistent protocol. Set against this, MW-LRC required an average of 72% memory overhead, compared to 10% overhead for the single-writer protocoIs.